IMPACT OF ALPHA SPIN NANOPARTICLES ON GENETIC DIVERSITY OFNIGERIA SESAME (Sesamum indicum L.) GERMPLASM (FULafia Journal of Science and Technology, 2025)
An experiment was carried out during the cropping season of 2025 in the Botanical Garden, Department of Plant Science and Biotechnology of Federal University of Lafia, Nasarawa State-Nigeria to investigate the influence of Alpha spin nanoparticles on the Genetic diversity of sesame. The seeds were exposed to Alpha pin Nanoparticles at 20min, 40min and 60min alongside the untreated (control). The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. Data were collected on the basis of plant height, Number of pods/plant, Number of seeds/pod, 1000seeds weight. Data collected were subjected to Analysis of Variance (ANOVA). The result revealed that most of the parameters were significant at 0≤ 0.05. Highest mean plant height was observed in variety FUTM9 (98.03), while OMA 40 (41.83) has the least plant height. The result also showed that FUTM7 (31.21) has the highest number of pods/plant while OMA 40, has the least number of pods/plant. FUTM9 (70.22) was observed to have the highest number of seeds/pod while Ex sudan (44.66) has the least number of seeds/pod. NAK033 has the highest dry seed weight (22.60) while FUTM9 has the least dry seed weight (3.89). Highest 1000seed weight was observed in the variety Jig 86 (8.80) while the least was observed in Ex sudan (6.79). Most of the varieties recorded their highest mean performance at T2 which is 40minutes of exposure to alpha nano spin particles. It is recommended that for most of the agronomic traits, T2 (40 minutes exposure time) be applied.